Gastroprotective effect and anti-apoptotic role of Lawsonia inermis extract against ethanol-induced gastric ulcers in Sprague Dawley - Muhammad Remy Othman,; Sayidah Asma Basir,; Khadher Ahmad,; Nur’ain Salehen,; Giribabu Nelli,; Rozana Othman,; Zulkifli Mohd Yusoff,; Syarifah Nur Syed Abdul Rahman,; Hazrina Hazni,; Khalijah Awang, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Lawsonia inermis (LI) or henna has been traditionally used since antiquity for cosmetics, medicinal and healing purposes including wound healing. Even so, the proof of the gastroprotective consequences of LI is inadequate while the pharmacological mechanisms continue to be scarce. The purpose of this research was to examine the acute toxicity and gastroprotective activities of Lawsonia inermis L. leaves ethanol:water (80:20) extract (LILEW) in contrast to ethanol-induced gastric ulcers within rats. The acute oral toxicity experiment was performed using Sprague Dawley female rats (n=6) for low dose (2000 mg/kg), and high dose (5000 mg/kg) as well as vehicle (distilled water). The gastroprotective result of LILEW was performed in an ethanol-induced ulcer inside Sprague Dawley rats (n=6). The animals were distributed among five groups namely ulcer control, normal control, drug control-omeprazole, high dose, and low dose of LILEW (500 mg/kg and 250 mg/kg, respectively). Acute toxicity experiments with LILEW on the rats did not demonstrate any signs of mortality and toxicity up to 5 g/kg suggesting that LILEW is safe to consume. The gastroprotective effect of LILEW at doses 250 mg/kg and 500 mg/kg, as well as omeprazole (20 mg/kg), showed significant rates of inhibition as much as 70.50±1.38% (drug control), 66.67±1.42% (low dose of LILEW) and 68.45±1.53% (high dose of LILEW) of rats attenuated gastric lesions that were generated by ethanol. In conclusion, these findings confirmed that Lawsonia inermis L. leaves ethanol: water extract is safe to consume and able to protect against gastric ulcers.